2021
DOI: 10.1007/s13593-021-00702-2
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and perspectives for beekeeping in Ethiopia. A review

Abstract: The honey bee is an important fruit and vegetable pollinator and a producer of honey and other hive products. Beekeeping is a sustainable and high-potential activity for local communities and especially for the rural poor to gain additional income through non-timber forest products, does not require much land or high starting costs, maintains biodiversity and increases crop yields. Ethiopia is one of the top ten honey and beeswax producers in the world, but plays only a minor role in the international honey tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 72 publications
(91 reference statements)
3
55
2
Order By: Relevance
“…Ethiopian national figures indicate 65% increase in the total number of honey bee colonies over the same period including a total of 3% frame hives in 2020 (CSA 2004(CSA , 2021. A recent review on an extended period based on FAOSTAT reported that number of colonies increased by 72% from 1993 to 2018 at national level (Gratzer et al 2021). Following the trends in production, honey export volume continued to grow from 274 tons in 2009, to 727 tons in 2012 and 883 tons in 2013 (Girma and Gardebroek 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ethiopian national figures indicate 65% increase in the total number of honey bee colonies over the same period including a total of 3% frame hives in 2020 (CSA 2004(CSA , 2021. A recent review on an extended period based on FAOSTAT reported that number of colonies increased by 72% from 1993 to 2018 at national level (Gratzer et al 2021). Following the trends in production, honey export volume continued to grow from 274 tons in 2009, to 727 tons in 2012 and 883 tons in 2013 (Girma and Gardebroek 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Following the trends in production, honey export volume continued to grow from 274 tons in 2009, to 727 tons in 2012 and 883 tons in 2013 (Girma and Gardebroek 2015). However, demands for honey bee pollination service of cultivated crops outpaced the growth in managed colony population in the country (Gratzer et al 2021), which indicate the need to further exploit the beekeeping potential.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, within the last decade, there has been a rapid increase in video-based counters income and combat unemployment. Ultimately, this could lead to improved protection of the environment and an increased quality of life and higher living standards in these countries (Gratzer, Susilo, Purnomo, Fiedler, & Brodschneider, 2019;Gratzer, Wakjira, Fiedler, & Brodschneider, 2021).…”
Section: Field Of Usementioning
confidence: 99%